Molecular Aspects of Drug-Induced Gingival Overgrowth: An In Vitro Study on Amlodipine and Gingival Fibroblasts - Lauritano, Dorina (Int J Mol Sci, 2019)
Gingival overgrowth is a serious side effect that accompanies the use of amlodipine. Several conflicting theories have been proposed to explain the fibroblast’s function in gingival overgrowth. To determine whether amlodipine alters the fibrotic response, we investigated its effects on treated gingival fibroblast gene expression as compared with untreated cells. Materials and Methods: Fibroblasts from ATCC(®) Cell Lines were incubated with amlodipine. The gene expression levels of 12 genes belonging to the “Extracellular Matrix and Adhesion Molecules” pathway was investigated in treated fibroblasts cell culture, as compared with untreated cells, by real time PCR. Results: Most of the significant genes were up-regulated. (CTNND2, COL4A1, ITGA2, ITGA7, MMP10, MMP11, MMP12, MMP26) except for COL7A1, LAMB1, MMP8, and MMP16, which were down-regulated. Conclusion: These results seem to demonstrate that amlodipine has an effect on the extracellular matrix of gingival fibroblast. In the future, it would be interesting to understand the possible effect of the drug on fibroblasts of patients with amlodipine-induced gingival hyperplasia.